The Use of Fingerboard Media to Improve the Ability to Count Addition Operations in Grade V Intellectual Disability Students at SDLB Sumber Dharma Malang City - Wiji Lestari; Ahsan Romadlon Junaidi; Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effectiveness of the fingerboard media on the ability to perform arithmetic addition operations on students with mild mental retardation. The research method used is quantitative with test data collection techniques and documentation. Meanwhile, the research design used was one group pre-test and post-test design. Data analysis used the Willcoxon Non-Parametric Test using the SPSS program. The subjects of this study were students with mild mental retardation at SLB Sumber Dharma, Malang City. The results showed that there was a change in student learning outcomes after being treated using the media of the fingerboard. This is shown by the Willcoxon hypothesis test data found Z count = -2.251 and α = 0.05, then sig = 0.024. This shows that Sig 0.024 is smaller than 0.05 (0.024 <0.05)